Information security and assurance International Conference, ISA 2011, Brno, Czech Republic, August 15-17, 2011. Proceedings - Kim, Tai-hoon; Adeli, Hojjat; Robles, Rosslin John; Balitanas, Maricel (Communications in computer and information science, 2011)
This book constitutes the proceedings of the International Conference on Information Security and Assurance, held in Brno, Czech Republic in August 2011.